The Effect of Fertilization Models and Silica Dosage on the Growth and Yield of Elongated Cherry Tomatoes (Solanum lycopersicum var. cerasiforme) - Aisyah Rosydana; Agus Miftakhurrohmat (CV. Media Digital Publikasi Indonesia, 2025)
This study aimed to evaluate the effect of fertilization models and silica dosage on the growth and yield of oval cherry tomatoes (Solanum lycopersicum var. cerasiforme). The study was conducted using a two-factor randomized block design (RBD) with four replicates. The first factor was the fertilization model (drip irrigation and spraying), and the second factor was the silica dose (0 cc/l [control], 1 cc/l, 2 cc/l, and 3 cc/l). The parameters observed included plant height, number of leaves, number of fruits, and fruit weight. The results showed that although statistically most treatments were not significantly different, drenching tended to be better in the early growth phase, while spraying produced higher fruit yields. Increasing the silica dose showed a positive trend for all parameters, with a dose of 3 cc/l producing the highest number and weight of fruits. These findings indicate that silica has the potential to increase cherry tomato productivity when applied with the appropriate model and dose.